Wacana Kesetaraan Gender dalam Keluarga pada Film Nanti Kita Cerita tentang Hari Ini : Analisis Wacana Kritis Norman Fairclough - Naurah , Nabila Zalfa; Siregar , Rachmi Kurnia (Jurnal Humaniora dan Ilmu Pendidikan, 2023)
Purpose: This study aims to find out how the discourse on gender equality in the family in the film "Nanti Kita Cerita Tentang Hari Ini". Methodology: The research is qualitative in nature using the Norman Fairclough critical discourse analysis method which consists of three dimensions, namely text (micro), discursive practice (meso), and social praxis (macro). The data analysis technique uses observation or direct observation by watching films repeatedly, supported by relevant data so that scenes depicting gender injustice in the film "NKCTHI" can be found associated with Norman Fairclough's critical discourse analysis. Results: The results of this study through three-dimensional critical discourse analysis, it was found that there is gender inequality in the family caused by the domination of power and the authoritarian role of the head of the family in each other family members related to patriarchal culture.